Current Awareness Services of the UP Main Library factor affecting the awareness of and utilization by users and implementation by librarians - Lanuza, Jonathan F. (2013)
Academic libraries remain as the only information centers of the university and keeping the users informed and updated is a critical function that the library must fulfil. The study focuses on the top mechanism for this function, Current Awareness Services, and the factors that affect the awareness and utilization of users and the implementation of the librarians. The research studied the users and the librarians of the UP Main Library.